Human–AI Collaboration in HR: Redefining Roles and Responsibilities in the Digital Workplace - Irum Jabeen; Hassaan Qureshi; Gulfam Arif; Saqib Tabussum; Muhammad Irfan Syed (Inverge Journal of Social Sciences, 2025)
The rapid digital transformation of organizations has significantly accelerated the adoption of artificial intelligence (AI) in human resource (HR) functions. This integration equips HR professionals with new roles, supported by AI-driven decision-making, automation, and workforce optimization. These evolving roles demand a blend of human expertise and technological skills. Understanding how human-AI collaboration enhances HR processes, performance, and future applications is crucial in the modern workplace. This study examines the impact of human-AI collaboration on HR effectiveness, role transformation, ethical concerns, and adoption willingness, while also exploring how professional experience influences perceptions of AI integration. A descriptive, quantitative research design was employed, using a structured questionnaire administered to 350 HR professionals across various sectors. The instrument measured five key constructs: Human-AI Integration, Efficiency and Performance Enhancement, Role and Responsibility Impact, Challenges and Ethical Considerations, and Future Perspectives and Adoption Intention. Data were analysed using descriptive statistics, correlation analysis, multiple regression, and one-way ANOVA. Findings indicate that HR professionals largely agree on AI's beneficial impact on efficiency, performance, and the future of the profession. Human-AI integration and efficiency enhancement were the strongest predictors of adoption intentions. However, ethical risks and implementation obstacles remain significant concerns, negatively influencing perceptions. Experience-based differences revealed that more seasoned professionals view AI integration more positively. HR is evolving into a more strategic, analytical, and human-oriented field through human-AI collaboration. While AI offers substantial benefits, successful adoption hinges on addressing ethical concerns and ensuring organizational preparedness. Sustainable collaboration requires enhancing digital competence, developing robust governance frameworks, and fostering a responsible approach to AI integration. References Afshar, M. Z., & Shah, M. H. (2025). A narrative review for revisiting BCG matrix application in performance evaluation of public sector entities. The Journal of Research Review, 2(2), 325–337. Afshar, M. Z., & Shah, M. H. (2025). Examining vision sharing as a driver of organizational resilience: Evidence from public sector contexts in developing economies. Indus Journal of Social Sciences, 3(2), 971–985. Al Karim, R. (2019). Impact of different training and development programs on employee performance in Bangladesh perspective. International Journal of Entrepreneurial Research, 2(1), 8–14. Ansari, F., Erol, S., & Sihn, W. (2018). Rethinking human-machine learning in industry 4.0: How does the paradigm shift treat the role of human learning? Procedia Manufacturing, 23, 117–122. https://doi.org/10.1016/j.promfg.2018.04.016 Arslan, A., Cooper, C., Khan, Z., Golgeci, I., & Ali, I. (2022). Artificial intelligence and human workers interaction at team level: A conceptual assessment of the challenges and potential HRM strategies. International Journal of Manpower, 43(1), 75–88. https://doi.org/10.1108/IJM-01-2021-0037 Asif, M., & Asghar, R. J. (2025). Managerial accounting as a driver of financial performance and sustainability in small and medium enterprises in Pakistan. Center for Management Science Research, 3(7), 150-163. https://doi.org/10.5281/zenodo.17596478 Asif, M., Shah, H., & Asim, H. A. H. (2025). Cybersecurity and audit resilience in digital finance: Global insights and the Pakistani context. Journal of Asian Development Studies, 14(3), 560-573. https://doi.org/10.62345/jads.2025.14.3.47 Asif, M., Pasha, M. A., & Shahid, A. (2025). Energy scarcity and economic stagnation in Pakistan. Bahria University Journal Of Management & Technology, 8(1), 141-157. Barile, S., Piciocchi, P., Bassano, C., Spohrer, J., & Pietronudo, M. C. (2018, June). Re-defining the role of artificial intelligence (AI) in wiser service systems. In International Conference on Applied Human Factors and Ergonomics (pp. 159–170). Springer International Publishing. https://doi.org/10.1007/978-3-319-93846-2_15 Butt, S. (2023). Employees’ perception regarding in-house training programs in Pakistani organizations. Journal of Workplace Behavior (JoWB), 4(1), 35–50. Butt, S., Mubeen, I., & Ahmed, A. (2022). Corporate social responsibility and firm financial performance: Moderating role of ethical leadership and social capital. JISR Management and Social Sciences & Economics, 20(1), 165–186. Ejaz, S. (2025). Leveraging machine learning techniques for enhancing signature verification to unveiling the forgery. Journal of Engineering and Computational Intelligence Review, 3(2), 96–114. Fenwick, A., Molnar, G., & Frangos, P. (2024). Revisiting the role of HR in the age of AI: Bringing humans and machines closer together in the workplace. Frontiers in Artificial Intelligence, 6, 1272823. https://doi.org/10.3389/frai.2023.1272823 Ijaz, S., & Zubair, M. T. (2025). A trust management-based energy efficient message scheduling algorithm in the internet of things system. Journal of Engineering and Computational Intelligence Review, 3(2), 51–67. Jain, R., Garg, N., & Khera, S. N. (2023). Effective human–AI work design for collaborative decision-making. Kybernetes, 52(11), 5017–5040. https://doi.org/10.1108/K-08-2022-1093 Kali, H. (2022). Redefining employee experience: The role of Workday HCM in workplace digitalization. International Journal of Engineering Science and Mathematics, 11(9), 1–6. Karim, M. M., Choudhury, M. M., & Latif, W. B. (2019). The impact of training and development on employees’ performance: An analysis of quantitative data. Noble International Journal of Business and Management Research, 3(2), 25–33. Latif, S. A., & Latif, A. (2025). Invisible walls: Uncovering healthcare access barriers for persons with disabilities in Bahawalnagar. Contemporary Journal of Social Science Review, 3(3), 942–951. Mer, A., & Virdi, A. S. (2023). Navigating the paradigm shift in HRM practices through the lens of artificial intelligence: A post-pandemic perspective. In The adoption and effect of artificial intelligence on human resources management, Part A (pp. 123–154). Emerald Publishing Limited. Naim, M. F. (2023). Reinventing workplace learning and development: Envisaging the role of AI. In The adoption and effect of artificial intelligence on human resources management, Part A (pp. 215–227). Emerald Publishing Limited. Pandya, B. (2019). A competency framework for virtual HR professionals in an artificial intelligence age. Mokslinės Leidybos Deimantas-Diamond Scientific Publication, 27–48. Patil, D. (2024). Human-artificial intelligence collaboration in the modern workplace: Maximizing productivity and transforming job roles. SSRN. https://doi.org/10.2139/ssrn.5057414 Rana, G., & Sharma, R. (2019). Emerging human resource management practices in Industry 4.0. Strategic HR Review, 18(4), 176–181. https://doi.org/10.1108/SHR-04-2019-0035 Riani, D. (2024). Reimagining human resource: Redefine human resource management practices for the future. Jurnal Riset Bisnis dan Manajemen, 17(1), 149–157. Sadia, M., Farid, S., & Latif, A. (2025). Parental resistance to vaccination in Kpk: A literature-based investigation. Contemporary Journal of Social Science Review, 3(2), 1429–1442. Shahinuzzaman, M., Shiva, T. A., Sumon, M. S., & Saifuddin, K. (2019). Mental health of women breast cancer survivor at different stages of the disease. Jagannath University J Earth Life Sci, 5(1), 1–12. Singh, A., & Pandey, J. (2024). Artificial intelligence adoption in extended HR ecosystems: Enablers and barriers. An abductive case research. Frontiers in Psychology, 14, 1339782. https://doi.org/10.3389/fpsyg.2023.1339782 Smith, S. S., Rohr, S. L., & Panton, R. N. (2018). Human resource management and ethical challenges: Building a culture for organization success. International Journal of Public Leadership, 14(2), 66–79. https://doi.org/10.1108/IJPL-08-2018-0033 Tasleem, N. (2018). Employee experience and HR innovation: Redefining human resource management through design thinking and human-centered practices. International Research Journal of Innovations in Engineering and Technology–IRJIET. Tiwari, R., Babu, N. S., Marda, K., Mishra, A., Bhattar, S., & Ahluwalia, A. (2024). The impact of artificial intelligence in the workplace and its effect on the digital wellbeing of employees. International Journal of Progressive Research in Engineering Management and Science (IJPREMS), 4(6), 2422–2427. Wang, J., & Pashmforoosh, R. (2024). A new framework for ethical artificial intelligence: Keeping HRD in the loop. Human Resource Development International, 27(3), 428–451. https://doi.org/10.1080/13678868.2023.2181372 Wang, Y., & Byrd, T. A. (2017). Business analytics-enabled decision-making effectiveness through knowledge absorptive capacity in health care. Journal of Knowledge Management, 21(3), 517–539. https://doi.org/10.1108/JKM-06-2016-0222 Wilkens, U. (2020). Artificial intelligence in the workplace–A double-edged sword. The International Journal of Information and Learning Technology, 37(5), 253–265. https://doi.org/10.1108/IJILT-01-2020-0002 Yabanci, O. (2019). From human resource management to intelligent human resource management: A conceptual perspective. Human-Intelligent Systems Integration, 1(2), 101–109. Zehir, C., Karaboğa, T., & Başar, D. (2019). The transformation of human resource management and its impact on overall business performance: Big data analytics and AI technologies in strategic HRM. In Digital business strategies in blockchain ecosystems: Transformational design and future of global business (pp. 265–279). Springer International Publishing. https://doi.org/10.1007/978-3-030-21906-0_13